PA 18-2-1347 Inflicted traumatic brain injury (ITBI) study- an hidden epidemic. (November 2018) - Viswanathan, Shankar; Kumar, Rashmi; Kumar, Chandrakanta; Pandey, Soumya; Kohli, Neera; Runyan, Desmond K
Abstract : Purpose: Data from India and other low and middle-income countries reveal high rates of the parental shaking in poor communities. Other Indian data reveal high rates of intellectual disability among children. The confluence of these observations provide an opportunity to understand the nature and consequences of potentially harmful child discipline techniques and TBI in young children. Methods: This matched case-control study includes 41 pair matched (age, sex, maternal age and education) children aged 2–6 years with evidence of intellectual disability (IQ<70), to examine the contribution of harsh discipline. Children with intellectual disabilities (cases) from pediatric developmental clinic and controls from pediatric well clinic were recruited at King George's Medical University, Lucknow, India. Parents were questioned about past discipline approaches using PCTS. Children received neurological exam, IQ tests and a MRI (Cases only). Distribution of patient characteristics were studied; prevalence of reported shaking and other discipline practices were estimated. MRI scans were reviewed and physical finding are presented. Results: Children's average age was 43.2 (16.3) months, 63% were boys. Average respondent parent age was 33 years (7.6), 45% had high school education. Forty-four percent reported definite; while other reported possible shaking. Nearly 80% reported shaking their children<2 years of age. The odds of developmental delay is 17 fold higher among parents reporting shaking compared to those who did not using exact conditional logistic regression. MRI scan revealed 66% having some sort of abnormalities. Conclusions: Parents report high rates of shaking among children<2 years as a discipline practice. The association observed between parents reporting shaking and developmental delay is large. Nearly 2/3 of all patients had some brain abnormality observed in MRI scan.